D | ||

((A → B) → C) → D |

0

Case | D | A | B | C | ((A → B) → C) → D |
---|---|---|---|---|---|

1 | T | T | T | T | T |

2 | T | T | T | F | T |

3 | T | T | F | T | T |

4 | T | T | F | F | T |

5 | T | F | T | T | T |

6 | T | F | T | F | T |

7 | T | F | F | T | T |

8 | T | F | F | F | T |

9 | F | T | T | T | F |

10 | F | T | T | F | T |

11 | F | T | F | T | F |

12 | F | T | F | F | F |

13 | F | F | T | T | F |

14 | F | F | T | F | T |

15 | F | F | F | T | F |

16 | F | F | F | F | T |

Public: **Yes**;
Show truth table: **Yes**;